2013
DOI: 10.1037/a0034269
|View full text |Cite
|
Sign up to set email alerts
|

Leader–team congruence in power distance values and team effectiveness: The mediating role of procedural justice climate.

Abstract: We examine the effect of (in)congruence between leaders' and teams' power distance values on team effectiveness. We hypothesize that the (in)congruence between these values would differentially predict team effectiveness, with procedural justice climate serving as a mediator. Using multisource data and polynomial regression, we found that similarities (and differences) between leaders' and their teams' power distance values can have consequential effects on teams' justice climate and, ultimately, their effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
263
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 182 publications
(272 citation statements)
references
References 68 publications
7
263
0
2
Order By: Relevance
“…() found that team performance was lowest when leaders perceived higher support climate than the team. Similarly, Cole, Carter and Zhang () found that the team performance was poorest when leaders' perceptions of power distance were higher than teams'. The differences between Gibson et al .…”
Section: Leaders' and Teams' Perceptionsmentioning
confidence: 93%
“…() found that team performance was lowest when leaders perceived higher support climate than the team. Similarly, Cole, Carter and Zhang () found that the team performance was poorest when leaders' perceptions of power distance were higher than teams'. The differences between Gibson et al .…”
Section: Leaders' and Teams' Perceptionsmentioning
confidence: 93%
“…Justice climate was also shown to mediate relationships between leadership attributes and individual level or team outcomes (e.g., Cole, Carter & Zhang, 2013;Stoverink, Umphress, Gardner, & Miller;Walumbwa, et al, 2010). In a moderator study, Yang, Mossholder and Peng (2007) found that unit-level procedural justice climate interacted with unitlevel power distance in explaining individual employees' organizational commitment and OCB after controlling for individual-level perceptions.…”
Section: The 2000 -2014 Era: Multilevel Research and Culture-climate mentioning
confidence: 99%
“…Era: Foundations of Construct Definition and Measurement Friedlander & Greenberg, 1971*Zohar, 1980Csoka, 1975Schneider, 1973Pfeifer & Schneider, 1974Bowen & Kilmann, 1975Drexler, 1977Schneider, 1972James, 1982Schneider & Hall, 1972Schneider & Snyder, 1975*James et al, 1984Gavin, 1975Cook et al, 19761986-1999 Ambrose et al, 2013Bobocel, 2013Cole et al, 2013Colquitt et al, 2013Stoverink et al, 2014 *Hartnell et al, 2011Gelfand et al, 2012Bezrukova et al,, 2012Gelfand et al, 2012 * NOTES: See the article's reference section for complete references. If the same citation appears in different columns, then the article had more than one focus.…”
mentioning
confidence: 99%
“…Research shows that when employees are involved in the decisionmaking process, they tend to be more engaged in work activities and exhibit higher job performance because they feel that their views are being considered and respected. 38 Communication, on the other hand, did not relate to any of the ProQOL scores. These factors, which simply relate to being informed by others, differ from the involvement measured by transformational leadership variables.…”
Section: Discussionmentioning
confidence: 52%